Glacial lake outburst flood (GLOF) modeling of Tsho Rolpa glacial lake, Nepal - R. B. Kayastha; S. Maskey (Proceedings of the International Association of Hydrological Sciences)
In recent decades, the Tsho Rolpa glacial lake has witnessed a significant increase in its surface area. Situated in the Eastern Himalayas at an elevation of 4552 m a.s.l. (meters above sea level), this lake has drawn attention due to the potential risks of glacial lake outburst floods (GLOFs). To comprehensively study and prepare for future GLOF events from Tsho Rolpa, advanced modeling techniques were employed, utilizing the National Weather Service BREACH (NWS-BREACH) and Hydrologic Engineering Center's River Analysis System (HEC-RAS) models. The assessment included the evaluation of dam breach scenarios, especially 20 and 40 m breaches, using the NWS-BREACH model to estimate breach hydrographs. This analysis revealed peak flow rates ranging from 8198 to 26 662 m3 s−1 for the respective breaching scenarios. Additionally, considering a change in the lake area over 20 to 40 years, the peak flow ranged from 8226 to 10 662 m3 s−1 for the 20 m breach scenario. The peak flow estimates obtained from NWS-BREACH were subsequently integrated into the HEC-RAS model to simulate peak discharge and flood heights at varying distances downstream of the lake outlet. To understand the consequences of a GLOF, the impact on downstream areas was assessed through flood inundation maps, and precautionary measures are recommended.